The Role of Parents in the Development of Akhlakul Karimah Elementary School Students in the Covid-19 Period - Muhajir, Muhajir; Sudarmi, Sudarmi (Pedagonal : Jurnal Ilmiah Pendidikan, 2023)
This study aims to describe the role of parents in the development of children's Ahlakul Karimah during the Covid-19 period for students, and describe what factors influence changes in children's morale during the Covid-19 period for students at school.The research method used in writing this thesis. This type of research is a qualitative type by analyzing the phenomena and meanings contained in Akhlakul karimah. The data were collected through interviews, observation and documentation, then the data were analyzed in several steps (1) utiliting (2) categorizing (3) data intervention, then the data was validated by (1) time extension (2) observation (3) tringulation. The results of the study show that the role of parents in the formation of children's character during the Covid-19 era is the change in attitudes and behavior that is good for students, as well as the formation of the values of honesty, discipline and responsibility, children maintain health in facing the future. Covid-19. Meanwhile, the teacher's strategy in dealing with the factors that influence changes in children's morals during the Covid-19 period is that parents and schools do not make Covid-19 an obstacle to accustom students to good behavior but work together to provide reinforcement in instilling morals in students not only by giving assignments and Submit assignments at the agreed time. However, instill the habit of honesty, discipline and responsibility.